1993
DOI: 10.1111/j.1752-7325.1993.tb02698.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Supplements in Caries Prevention: A Literature Review and Proposal for a New Dosage Schedule

Abstract: Fluoride supplements have contributed significantly to caries prevention; however, better information about the dynamic nature of fluoride's effect on caries has made a reappraisal desirable. It seems, from a review of the literature, that the benefit from supplement use that can be expected today in populations in low-fluoride areas is small. Possible reasons include the low caries incidence in children of recent years. Few people are willing to use supplements with sufficient regularity to achieve an effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 105 publications
0
32
0
Order By: Relevance
“…Because most supplements sold in Norway were lozenges designed to be retained in the mouth for several minutes, this association was likely due to a local, post-eruptive effect of the fluoride in the lozenges, which are retained in the mouth for some time (6,(24)(25)(26). Recent literature tends to deny any substantial preeruptive effect of supplements and to downplay any post-eruptive effect in those studies where socio-economic and lifestyle factors were taken into account (1,5). Recent literature tends to deny any substantial preeruptive effect of supplements and to downplay any post-eruptive effect in those studies where socio-economic and lifestyle factors were taken into account (1,5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because most supplements sold in Norway were lozenges designed to be retained in the mouth for several minutes, this association was likely due to a local, post-eruptive effect of the fluoride in the lozenges, which are retained in the mouth for some time (6,(24)(25)(26). Recent literature tends to deny any substantial preeruptive effect of supplements and to downplay any post-eruptive effect in those studies where socio-economic and lifestyle factors were taken into account (1,5). Recent literature tends to deny any substantial preeruptive effect of supplements and to downplay any post-eruptive effect in those studies where socio-economic and lifestyle factors were taken into account (1,5).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the low levels of ambient fluoride in Norway, it is reasonable to say that there is no halo effect because there is no water fluoridation anywhere in the region. Children of lower socioeconomic status might derive a benefit from using supplements, but many studies have shown that compliance is poorer in such social groups, making supplements a poor public health measure (1,29). We know that children of higher socio-economic status are most likely to use fluoride supplements (27).…”
Section: Discussionmentioning
confidence: 99%
“…To eliminate fluorosis with TF score 3, and to reduce significantly the prevalence of fluorosis with TF score 2, are achievable goals if consumer behavior can be changed. Strategies should include a reduction in toothpaste ingestion or more widespread use oflow-fluoride toothpaste by infants (Horowitz, 1992), promotion of the availability of fluoride-free infant formula (Pendrys and Stamm, 1990), and reduced use offluoride supplements (Riordan, 1993b).…”
Section: Discussionmentioning
confidence: 99%
“…These include ingestion of fluoridated toothpaste (Beltran and Szpunar, 1988;Horowitz, 1992;Riordan, 1993a), the use of fluoride supplements (Pendrys and Morse, 1990;Szpunar and Burt, 1992;Riordan, 1993b), and infant formulae manufactured in fluoridated areas and prepared using fluoridated water [recently reviewed by Burt (1992)]. In communities in industrialized countries in which dental fluorosis has been reported, one likely cause of the fluorosis is compliance with fluoride regimens advocated by dental professionals for the prevention of caries (Pendrys and Katz, 1989).…”
mentioning
confidence: 99%
“…He came to the conclusion that fluoride supplements are not particularly effective because of compliance problems. It should also be taken into account that fluoride supplementation increases the risk of fluorosis [Thylstrup et al, 1979;Riordan, 1993Riordan, , 1999.…”
mentioning
confidence: 99%